Зарни чорыг: повестьёс, веросъёс / Петр Куликов - Куликов Петр Васильевич (Удмуртия, 1992)
Экземпляры: (20240409) / Инвентарный номер: 22428 / Цена: 45.00 / Сис.шифр: 84(2=664.1) / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2=664.1)